Penanaman Nilai-Nilai Karakter Peserta Didik Melalui Ekstrakurikuler Pramuka - Novri Gazali; Romi Cendra; Oki Candra; Leni Apriani; Idawati Idawati (Universitas Muhammadiyah Surabaya, 2019)
The activities of the Community aims to provide planting character values learners through extracurricular Scouts in SMK Negeri 1 Rokan IV Koto, Rokan Hulu .Through character education, expected the learners are able to independently increase and use his knowledge, review and internalize and personalize the character values and morals noble so manifest in behavior everyday. Kegiatan community service societies was held at SMK Negeri 1 Rokan IV Koto, Rokan Hulu with p eserta is a student extracurricular Scout SMK Negeri 1 Rokan IV Koto, Rokan Hulu totalling 14 person. Material naturald this activity about the scope of the national character that must be ditanamakan against the students, who include 18 characters. As for the entire characters are: religious, honest, tolerant, disciplined, hard working, creative, independent, democratic, curiosity, passion, love of the fatherland, to appreciate the achievements, friendly/communicative, peace-loving, an avid reader, care for the environment, social care, and responsibility. This activity has many benefits for students that is shaping the character of the students, make students become more appreciative fellow, trained mentally and also the moral of the learners.